POLA KEMITRAAN KERJASAMA OPERASIONAL AGRIBISNIS (KOA) ANTARA KELOMPOK TANI SUMARAH DENGAN PT. PAGILARAN DI DUSUN NGAWIS 2 DESA NGAWIS KECAMATAN KARANGMOJO KABUPATEN GUNUNGKIDUL - Fitria Sukma Nasucha; Daru Retnowati; Vandrias Dewantoro (Jurnal Dinamika Sosial Ekonomi, 2015)
The aim of this study is 1) to analyze the amount of profit pattern koa partnership between the cocoa farmers group Sumarah with PT. Pagilaran in Ngawis Village 2, 2) to know how far the effectiveness partnership of the PT. Pagilaran with cocoa farmer groups Sumarah in Ngawis village 2. The method used in this study is Descriptive. The study sample as many as 44 respondents had taken using Census method. The data used is primary data obtained from interviews of farmers in the Ngawis village and questionnaires filled out by respondents were concerned, the secondary data obaatained by quoling existing data from agencies associated with the research. The analytical techniques to determine the effectiveness of the Partnership by using the Likert Scale method and the analysis technique used to determine the advantages of using profit analysis. The study results show that cacao farmer effort Sumarah farmer group with PT Pagilaran in the Ngawis village 2, the Ngawis, Karangmojo Sub-District, Gunungkidul benefit to the Sumarah cacao farmer group that is equal to Rp 737.458.34/1.38 ha. The Effectiveness partnership that carried out between a Sumarah farmer group with PT. Pagilaran effectiveness hight, that is with the score 20.1 (83.759%). Keywords: Profits cacao farmer group, effectiveness partnership, and The Operational Agribusiness Cooperation (OAC) Partnership